Experimental evaluation of silicon photonics transceiver operating at 120°C for 5G antenna array systems. Issue 24 (1st November 2018) - Testa, F.; Giorgi, L.; Bigongiari, A.; Bianchi, A.
Abstract : The use of optical transceivers in antenna array system applications requires reliable operation at high temperature. The experimental characterisation of a silicon photonics transceiver operating in a harsh environment with temperatures up to 120°C is presented and discussed. The transceiver was placed inside a climatic chamber and it was fed by an external depolarised light source. The bit error rate was measured, and the impacts on transmission performances were analysed and discussed, including reliability aspects. The authors believe that silicon photonics transceivers with an optimised design and with improvements in the optical connector and fibre adhesive technology are suitable for this kind of applications.